Evolution of Dada Uttam Kumar: Performing Masculinity and the Disillusioned Bhadralok Mahanayak in the 1970s' Popular Melodramas. (June 2019) - Banerjee, Smita
This essay focuses on a fragment of the Bengali superstar Uttam Kumar's star text, the dada figure, to analyse the contours of melodramatic enunciations and masculinity that appear in the 1970s' popular films. This decade is identified with the radical politics associated with the Naxal movement that erupted in varied expressions of rage and anger at institutional and systemic failures. Since Uttam typified a bhadralok masculine subjectivity, his evolution in domestic melodramas especially in male weepies from the period enables me to read the specifics of regional cinema and its response to social and political contexts of the times.